Impact of the COVID-19 pandemic on the emergency transportation of older patients: a population-based descriptive study in Osaka prefecture, Japan - Tanaka, Kenta; Katayama, Yusuke; Kitamura, Tetsuhisa; Domi, Hisaya; Oda, Jun; Matsuoka, Tetsuya (Frontiers in Public Health, 2025)
BackgroundThis study aimed to assess the influence of the COVID-19 pandemic on emergency medical services for older patients who were transported to hospitals by ambulance.MethodsThis descriptive retrospective study was conducted between January 2019 and December 2022, using the Osaka Emergency Information Research Intelligent Operation Network system. All patients aged ≥65 years who were transported by ambulance to hospitals in Osaka Prefecture for acute diseases were included. The outcomes were the number of older patients transported by ambulance, the number of difficulties obtaining patient acceptance at hospitals, and the number of deaths following hospitalization. We calculated the incidence rate ratio (IRR) and its associated 95% confidence interval (CI) for each year of the study period (2020, 2021, and 2022) using Poisson regression, with 2019 as the control year.ResultsCompared to 2019, the numbers of older patients transported for acute disease were 186,218 (IRR, 0.92; 95% CI: 0.92–0.93) in 2020, 186,955 (0.93, 0.92–0.93) in 2021, and 214,048 (1.06, 1.05–1.07) in 2022. Difficulty obtaining patient acceptance increased over time (6,668 in 2020, 9,894 in 2021, and 22,790 in 2022). The number of deaths were 8,660 (1.01, 0.98–1.04) in 2020, 9,754 (1.14, 1.10–1.17) in 2021, and 11,050 (1.29, 1.25–1.32) in 2022.ConclusionThe number of older patients transported to emergency departments in Osaka Prefecture for acute diseases increased in 2022 compared with 2019. Difficulties obtaining patient acceptance and in-hospital deaths also increased over this period.